Response to Zoledronic Acid Infusion in Children With Fibrous Dysplasia - Tripathy, Sujit Kumar; Swaroop, Shakti; Velagada, Sandeep; Priyadarshini, Debashree; Das, Rashmi Ranjan; Satpathy, Amit Kumar; Agrawal, Kanhaiyalal (Frontiers in Pediatrics, 2020)
Objective: This retrospective study evaluated the outcome and safety of long-term treatment with zoledronic acid, in both polyostotic and mono-ostotic fibrous dysplasia (FD) of children. Methods: The case-records of children and adolescents with symptomatic FD who received zoledronic acid (0.1mg/kg IV infusion over one hour) and have completed at least 2-years follow up were analyzed. The relevant details were recorded in a predesigned chart. Clinical assessment (pain assessment by visual analogue scale, VAS and incidence of new fracture), radiological changes (cortical thickening, ossification and decrease in the diameter of the osteolytic lesions) and biochemical parameters (alkaline phosphatase, ALP) were used to evaluate the improvement. Results: The mean age of presentation was 9.1 years, with four males and six females. All patients had symptomatic FD in the lower limb with complaints of pain, tenderness, swelling or deformity. Four children had associated pathological fracture. The radiological evaluation with bone scan revealed polyostotic involvement in 8 patients and mono-ostotic involvement in 2 patients. Three patients had associated systemic features like café-au-lait spots or precocious puberty. The fracture united within three months and the radiological improvement was evident in the form of filling of the osteolytic defect. The pain score in six patients showed significant improvement (VAS <3). The ALP level decreased to 544.12 + 47.35 IU/L from an initial value of 895.75 + 79.64 IU/L (p=0.04) at 12 months. One patient had symptomatic hypocalcaemia after Zoledronic acid infusion. Conclusion: The clinical and radiological response of zoledronic acid treatment in FD of children is promising. Further randomized control trials with a larger sample size are required to establish this drug as a frits-line medical treatment in FD.